Health‐Related Quality of Life in Survivors of High‐Risk Neuroblastoma After Stem Cell Transplant: A National Population‐Based Perspective. Issue 9 (20th May 2016) - Portwine, Carol; Rae, Charlene; Davis, Jeff; Teira, Pierre; Schechter, Tal; Lewis, Victor; Mitchell, David; Wall, Donna A.; Pullenayegum, Eleanor; Barr, Ronald D.
Abstract : Purpose: This study aimed to estimate the burden of morbidity, in terms of health‐related quality of life (HRQL), in survivors of high‐risk neuroblastoma (NBL) after myeloablative chemotherapy followed by autologous hematopoietic stem cell transplant (HSCT). Patients and methods: A national population‐based survey was undertaken of survivors of high‐risk NBL (N = 99), diagnosed between 1991 and 2010 and treated with HSCT. Parents completed a proxy questionnaire incorporating two HRQL measures, Health Utilities Index (HUI) 2 and 3. Children >12 years of age provided self‐assessments. Clinical and demographic data were collected. Independent t ‐test and one‐way analysis of variance were used to assess differences. Comparative data were obtained from previously published work and Statistics Canada's 1998 National Population Health Survey. Results: On a scale of 0 (being dead) to 1.0 (perfect health), mean HRQL utility scores were 0.89 (SD = 0.11) in HUI2 and 0.84 (SD = 0.18) in HUI3. Parents reported morbidity in sensation (52.5%), pain (30.3%), cognition (28.0%), and emotion (24.2%) in HUI2 and in hearing (38.4%), pain (30.3%), cognition (27.3%), and speech (23.2%) in HUI3. HRQL was not significantly different compared to NBL survivors treated without HSCT, but was less than in nontransplanted survivors of acute lymphoblastic leukemia and Wilms tumor, and children in the general population, yet higher than in survivors of brain tumors. Conclusions: HRQL is compromised in high‐risk NBL survivors treated with and without HSCT. A differential effect on hearing reflects additional exposure to platinum‐based chemotherapy. These results should inform long‐term care and the development of new therapeutic interventions.